MANAJEMEN OPERASI SYARIAH: IMPLEMENTASI DI UMKM - Najwa, Alyasa; Putri, Fauziyah Mulyana; Comersyah, Lanifa Fauzia; Ramdani, Sabrina Oktavia (Taksasila Edukasi Insani, 2024)
This research discusses the implementation of sharia operational management in Micro, Small and Medium Enterprises (MSMEs) in order to increase business efficiency and sustainability in accordance with sharia principles. The aim of this research is to provide MSMEs with an in depth understanding of operational management principles that are in accordance with sharia values and management. This research uses literature and literature research methods by examining material related to the principles and management of sharia operational management. The research results show that the implementation of sharia operational management in MSMEs is able to have a positive impact on increasing profitability and operational efficiency. However, obstacles are still found in terms of understanding sharia principles and in sharia-based management. Therefore, operational management skills training and the application of sharia principles are needed to encourage sharia-based MSMEs in Indonesia. Keywords : Sharia Operational Management, MSMEs, Sharia Principles.